KNOWLEDGE AND ATTITUDES TOWARD REPRODUCTIVE HEALTH ARE ASSOCIATED WITH CYBERSEX ACTIVITIES AMONG ADOLESCENTS - Destiana Angie Callista Putri; Nina Hidayatunnikmah; Nyna Puspita Ningrum (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Cybersex is a form of sexually related behaviour conducted through the internet and has become increasingly prevalent among adolescents due to widespread access to digital technology. Adolescents' knowledge and attitudes regarding reproductive health may influence their engagement in cybersex activities. This study aimed to examine the association between reproductive health knowledge and attitudes and cybersex activities among adolescents. An analytical observational study with a cross-sectional design was conducted among 110 adolescents aged 17–19 years at SMK Pawyatan Daha 1 Kediri. Participants were selected using simple random sampling. Data were collected using a structured questionnaire assessing the frequency and types of cybersex activities, reproductive health knowledge, and attitudes towards reproductive health issues, including contraceptive use and sexually transmitted infections. Data were analysed using Spearman's rank correlation test. Spearman's correlation analysis demonstrated a significant association between cybersex activities and reproductive health knowledge (p0.001; r=0.579), as well as between cybersex activities and reproductive health attitudes (p0.001; r=0.582). The correlation coefficient indicated that attitudes toward reproductive health showed a slightly stronger association with cybersex activities than knowledge.Reproductive health knowledge and attitudes were significantly associated with cybersex activities among adolescents. Strengthening reproductive health education and promoting positive attitudes may help adolescents make healthier decisions regarding online sexual behaviour.